Instructors' gestures enhance their teaching experience and performance while recording video lectures. (29th November 2019) - Yang, Jiumin; Zhu, Fangfang; Guo, Peiyu; Pi, Zhongling
Abstract: An instructor's gestures have an effect not only on students' learning but also on teaching itself. In two experiments, this study tested whether instructors' use of gestures while recording video lectures affected their teaching performance, stress, and cognitive load. In Experiment 1, participants recorded video lectures with gestures or without gestures. As hypothesized, t tests showed that participants in the gestures condition had better teaching performance and lower cognitive load than participants in the no‐gestures condition, whereas there was no effect on stress level. In Experiment 2, participants recorded video lectures with either pointing gestures or representational gestures. The t tests indicated that participants in the pointing gestures condition showed better teaching performance and experienced lower stress than those in the representational gestures condition, but there was no difference in cognitive load. Overall, our findings suggest that in the new educational environment of video lectures, instructors should consider using gestures, especially pointing gestures, to improve their teaching and their experience of teaching. Lay Description: What is already known about this topic Instructors' gestures have benefits on learners' learning. Different types of gestures have different effect. Gestures can affect speaker's cognition. What this paper adds This study explored the effect of whether instructors' gestures and different types of gestures (pointing gestures and representational gestures) during recording instructional videos on their teaching. Instructors' gestures improved their teaching performance, induced cognitive load, and enhanced teaching efficacy. Instructors' pointing gestures were outperformed than representational gestures in teaching performance and stress level. Implications for practice and/or policy Instructors should consider using gestures when recording instructional videos, especially pointing gestures.